Hubungan Masa Kerja, Kebiasaan Merokok dan Olahraga dengan Kapasitas Vital Paru Polisi Lalu Lintas di Wilayah Kerja Polres Sleman - Saprinda Nurin Agassi; Heru Subaris Kasjono; Mohammad Mirza Fauzie (Poltekkes Kemenkes Yogyakarta, 2018)
Air pollution causes serious negative impact on human health, especially for lung as the respi-ratory organ. Other than air pollution, cigarette smoke can also affect human health because active smokers may have two to four times risk of getting coronary heart disease and may possess higher risk to suffer from lung cancer. One of the professions which are highly suscep-tible to have risk of getting lower function of lung is traffic policeman. The objective of this re-search was to find out the correlation between working period, smoking habit, and physical exercises of Sleman’s traffic policemen and their lung vital capacity (LVC), by conducting an analytical survey with cross sectional design. The number of study subjects is 49. The data of working period, smoking habit and physical exercises were obtained by using questionnaire; meanwhile, the data of LVC were measured by using spirometer. The data were analysed by employing Spearman Rank test at ?=0,05. Based on the study results u can be conclude that the LVC has no significant correlation with working period (p-value=0,924), smoking habit (p- value=0,307), and physical exercises (p-value= 0,468).